THE RELATION BETWEEN LEARNING ACTIVITY, PEER ENVIRONMENT, INTEREST TO LEARN AND MATHEMATICS LEARNING OUTCOMES - Kurnia Nopitasari; Uswatun Khasanah (Universitas Ahmad Dahlan, 2019)
Low students' learning outcomes are related to many factors. Learning activities, peer environment, and interest in learning are among them. This study aims to determine whether there are positive and significant relations between learning activity, peer environment. Interest in learning and mathematics learning outcomes of grade X Office Administration students of Vocational High School (SMK) Muhammadiyah 2 Yogyakarta in the odd semester of the academic year of 2017/2018. This study's population were regular grade X Office Administration students of SMK Muhammadiyah 2 Yogyakarta in 2017/2018, consisting of two classes with 58 students. A random sampling technique was applied to take this research sample, a grade X Office Administration student's class 2. The data on learning activity, peer environment, and interest to learn were obtained through questionnaires. At the same time, the data of the mathematics learning outcomes were obtained through the test. The research instruments were tested using a validity test, differential test, and reliability test. Analysis prerequisite tests include normality, linearity, and independence test. Product moment and multiple linear regression analysis were used to analyze the data. The results show that there are not positive and significant relations between learning activity, peer environment. Interest to learn with mathematics learning outcomes of grade X Office Administration students of SMK Muhammadiyah 2 Yogyakarta in the odd semester of the academic year of 2017/2018. The results are evident in Fount Â Ftable which is 0,209 > 3,100 with R = 0,177 and R2 = 0,031 with , with SR = , RC = Â and RC = -1,734 , EC = , EC = Â and EC = .